Analysis of Factors Affecting Dividend Policy in the IDX High Dividend 20 Companies Listed on the Indonesia Stock Exchange (IDX) During the Period of 2019-2023 - Irkham, Nuriyah; Hartono, Ulil; Haryono, Nadia Asandimitra (Transpublika Publisher, 2025)
Deciding on how to distribute net income to shareholders or reinvest it for business operations is a crucial strategic move known as dividend policy. The focus of this research is to examine the influencers affecting dividend policy within businesses listed in the IDX High Dividend 20 on the Indonesia Stock Exchange from 2019 to 2023. The analyzed factors consist of the current ratio, debt-to-equity ratio, return on assets, and firm size. A quantitative method with a descriptive-analytical framework is utilized in the study. Information is gathered from the yearly financial statements of 18 chosen businesses from the total of 20 companies in the IDX High Dividend 20 group. Information gathering is carried out using various record-keeping techniques, while an assortment of linear regression is utilized for data examination. It has been revealed through the findings that the proportions of the present resources to liabilities and the magnitude of the company do not notably impact how dividends are managed. Conversely, the level of debt relative to equity and the return generated on assets have a notable beneficial impact on the dividend strategy. The calculation of the determination coefficient presents that approximately 14% of the fluctuation in dividend strategy can be accounted for by the independent factors, with the rest being influenced by external elements not covered in this research. This research contributes to understanding the factors influencing dividend policy in Indonesia, particularly among companies that focus on high dividend distribution.